Adolescent exposure to food and beverage marketing on social media by gender: a pilot study - Ashley Amson; Elise Pauzé; Lauren Remedios; Meghan Pritchard; Monique Potvin Kent (Cambridge University Press, 2023)
Abstract Objective: The objective of this research was to determine if, based on gender, adolescents were exposed to different marketing techniques that promoted food and beverages over social media. Design: A secondary analysis of adolescent boy (n 26) and girl (n 36) exposures (n 139) to food and beverage marketing was conducted. Mann-Whitney U and Fisher's exact tests were conducted to compare the number, healthfulness and the marketing techniques of exposures viewed by boys and girls. Setting: Ottawa, Ontario, Canada. Participants: Sixty-two adolescents aged 12-16 years. Results: Boys and girls were exposed to similar volumes of food marketing instances (median = 2 for both boys and girls, Mann-Whitney U = 237, P = 0·51) per 10-min period of social media use. More girls viewed products that were excessive in total fat compared to boys (67 % v. 35 %, P = 0·02). Boys were more likely to view instances of food marketing featuring a male as the dominant user (50 % v. 22 %, P = 0·03), appeals to achievement (42 % v. 17 %, P = 0·04), an influencer (42 % v. 14 %, P = 0·02) and appeals to athleticism (35 % v. 11 %, P = 0·03), whereas girls were more likely to view instances of food marketing featuring quizzes, surveys or polls (25 % v. 0 %, P = 0·01). Conclusions: Food and beverage companies utilise marketing techniques that differ based on gender. More research examining the relationship between digital food and beverage marketing and gender is required to inform the development of gender-sensitive policies aimed at protecting adolescents from unhealthy food marketing.